A Review of Chronic Pain and Device Interventions: Benefits and Future Directions - Cain W. Stark; Mir Isaamullah; Shareef S. Hassan; Omar Dyara; Alaa Abd-Elsayed (Pain and Therapy, 2022)
Abstract Chronic pain is a debilitating condition with a growing prevalence both in the USA and globally. The complex nature of this condition necessitates a multimodal approach to pain management that extends beyond the established pharmaceutical interventions currently employed. A variety of devices comprising both invasive and noninvasive approaches are available to patients, serving as adjuvants to existing regimens. The benefits of these interventions are notable for their lack of addiction potential, potential for patient autonomy regarding self-administration, minimal to no drug interaction, and overall relative safety. However, there remains a need for further research and more robust clinical trials to assess the true efficacy of these interventions and elucidate if there is an underlying physiological mechanism to their benefit in treating chronic pain or if their effect is predominantly placebo in nature. Regardless, the field of device-based intervention and treatment remains an evolving field with much promise for the future chronic pain management.